Synergistic effects of nano-silica on aluminum diethylphosphinate/polyamide 66 system for fire retardancy. (March 2016) - Zhan, Zhaoshun; Li, Bin; Xu, Miaojun; Guo, Zhanhu
Nano-silica had been used as a synergistic agent for the preparation of aluminum diethylphosphinate (AlPi) flame retardant polyamide 66 (PA66/AlPi) and PA66/AlPi/nano-silica composites through twin-screw extrusion. The limiting oxygen index (LOI), used to characterize the minimum amount of oxygen needed to sustain a candle-like flame, revealed that the PA66/10%AlPi/1%nano-silica composites exhibited an excellent flame retardant efficiency with a high LOI value of 32.3%. The vertical flame test (UL-94) revealed that the PA66/10%AlPi/1%nano-silica composites passed the V-0 rating without drop melting. Cone calorimeter test revealed that the heat release rate and total heat rate for the PA66/10%AlPi/1%nano-silica composites were significantly decreased by 51.1 and 16.8%, respectively, compared with those of pure PA66. The thermogravimetric analysis showed that the PA66/10%AlPi/1%nano-silica composites had vast chars of 8.1% even at 800°C, indicating that nano-silica could promote the char formation of the PA66 composites. Scanning electron microscopy indicated a solid and tough residue of the burned PA66/10%AlPi/1%nano-silica composites as compared with the very loose and brickle residue of the burned pure PA66, indicating that a suitable amount of nano-silica played a synergistic effect in the flame retardancy.